2019
DOI: 10.1007/s10120-019-00944-w
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer mortality rates among US and foreign-born persons: United States 2005–2014

Abstract: Background Historically, foreign-born individuals in the US have had an elevated risk of dying from gastric cancer when compared to US-born individuals. This is primarily due to factors that occur prior to their immigration to the US, including diet and underlying risk of H. pylori infection. Methods National mortality data from 2005 to 2014 were obtained from the CDC's National Center for Health Statistics. Annual population estimates were obtained from the US Census Bureau's American Community Survey for for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…While these distinct racial/ethnic incidence patterns in NCGC and CGC are established, few studies have compared differences in survival and mortality trends among racial/ethnic groups in these cancer subtypes. Several studies assessed survival and death certificate mortality in gastric cancer overall, yielding mixed results 6‐13 . Some showed no differences, while others showed higher survival among Asians/Pacific Islanders and inconsistent outcomes in Hispanics 6‐10 …”
Section: Introductionmentioning
confidence: 99%
“…While these distinct racial/ethnic incidence patterns in NCGC and CGC are established, few studies have compared differences in survival and mortality trends among racial/ethnic groups in these cancer subtypes. Several studies assessed survival and death certificate mortality in gastric cancer overall, yielding mixed results 6‐13 . Some showed no differences, while others showed higher survival among Asians/Pacific Islanders and inconsistent outcomes in Hispanics 6‐10 …”
Section: Introductionmentioning
confidence: 99%
“…As we know above, this result is relatively stable and reliable. Besides, we have evidence that some studies have shown that the death risk of gastric cancer was highest among Asians/Paci c Islanders, followed by Blacks and was least common in Whites [48,49]. This difference may be due to the higher survival rate of white gastric cancer patients dying from other causes than gastric cancer [10,50], and the difference between white and African Americans can be generalized to the difference between other races and whites.…”
Section: Discussionmentioning
confidence: 91%
“…Gastric cancer (GC) is the second leading cause of cancer-related death worldwide ( Hallowell et al, 2019 ; Liou et al, 2020 ). Chronic atrophic gastritis (CAG) is a chronic gastric mucosal inflammation associated with the loss of gastric glandular cells, replaced by intestinal-type epithelium and fibrous tissue ( Tian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%